Economics, entropy and the environment the extraordinary economics of Nicholas Georgescu-Roegen - Beard, T. Randolph (Edward Elgar, 1999)
This extraordinary book provides a critical review of the work of Nicholas Georgesçu-Roegen in conventional economics, environmental economics and methodology. Particular attention is paid to the role of thermodynamics in Georgesçu-Roegen's economics.